The Reality of Internal Auditing in Activating Governance Mechanisms in Saudi Public Sector - Bu haya, Mohammed; Al Ruhiman, Munira (The Arab Journal of Administration, 2025)
The study aimed to identify the reality of internal audit in activating governance mechanisms in the Saudi public sector, enhancing the importance of governance in the government sector under effective internal audit practices. To achieve the objectives of the study, the descriptive quantitative approach was used and the survey strategy was chosen to analyze the data in order to reach valuable indications and indicators that support the study, The study sample represents a random sample of directors of internal audit departments, internal auditors and accountants in the Saudi public sector, and the questionnaire was relied on as a tool for the study. The SPSS was used to analyse the results. The results of the study concluded that there is awareness of modern concepts in the Saudi environment, especially with the changes and transformations in application of the Kingdom's Vision 2030. The internal auditor also plays an important role in developing the effectiveness and efficiency of the internal control environment, which is reflected in the more efficient and effective application of governance mechanisms. The study recommended measuring the impact of the application of governance mechanisms in the presence of an effective internal review by developing specific indicators to monitor progress.